Hispano-Moresque ceramic tiles from the Monastery of Santa Clara-a-Velha (Coimbra, Portugal) - Coentro, Susana (2015)
A group of late 15th–early 16th century Hispano-Moresque glazed tiles from the Monastery of Santa Clara-a-Velha, in Coimbra, were, for the first time, characterised chemically and morphologically. Since the prevailing idea among art historians in Portugal is to judge the Hispano-Moresque tile heritage as Spanish production, the findings concerning technological processes were compared with the Islamic technology in the Iberian Peninsula and latter Hispano-Moresque in Spain. This study is the first analytical indicator of a production technology with some differences from the Hispano-Moresque workshops (such as Seville, Toledo, etc.) and points out to a possible local production. Five different coloured glazes were identified: white, blue, green, amber and black, all displaying high-lead content, as expected for this type of ceramics. Tin oxide was identified in high contents (7–14 wt.%) in white and blue glazes, its crystals homogenously distributed in also very homogeneous glazes, showing similarities with an Islamic glazing technology. On the other hand, Ca-rich thick glaze–ceramic interfaces were observed, with many mineral inclusions (wollastonite (CaSiO3) and also K-feldspars (general formula KAlSi3O8), showing a higher resemblance with a later Hispano-Moresque technology. Other compounds were also identified from reactions involving the colour compound: malayaite (CaSnOSiO4), bustamite (CaMnSi2O6), braunite ((Mn2+, Mn3+)6O8SiO4), andradite (Ca3Fe2Si3O12), magnesioferrite (MgFe2O4) and a nickel ferrite (NiFe2O4). The chemical composition of this glaze–ceramic interface suggests firing temperatures between 950 °C and 1000 °C and its thickness implies a single-fire process. The chemical characterisation does not suggest different recipes or different firing processes for cuerda seca and arista tiles.